Strictly Dynamite The Sensational Life of Lupe Velez - Golden, Eve (Screen classics (Lexington, Ky.), 2023)
"Before Salma Hayek, Eva Longoria, and Penelope Cruz, there was Lupe Velez-one of the first successful Latin-American Hollywood stars, who swept past the xenophobia of Old Hollywood to pave the way for future icons from around the world. Her career began in the silent era when her beauty was enough to make it onto the silver screen, but with the rise of talkies, Velez could no longer hope to hide her Mexican accent. Yet Velez proved to be a talented dramatic and comedic actress (and singer) and was much more versatile than such legends as Greta Garbo, Katharine Hepburn, and Gloria Swanson. Velez starred in such films as Hot Pepper (1933), Strictly Dynamite (1934), and Hollywood Party (1934). In the 1940s, Velez's popularity peaked after appearing as Carmelita Fuentes in eight Mexican Spitfire films, a series created to capitalize on Velez's well-documented fiery personality. Nicknamed "the Mexican Spitfire" by the media, Velez's personal life was as colorful as her screen persona. Fan magazines mythologized her mysterious childhood in Mexico, while mainstream publications obsessed over the drama of her romances with such figures as Gary Cooper, Erich Maria Remarque, and John Gilbert, along with her stormy marriage to Johnny Weissmuller. In 1944, a pregnant and unmarried Velez died of an intentional drug overdose. Her tumultuous life and the circumstances surrounding her early death have been the subject of speculation and controversy. In Strictly Dynamite: The Sensational Life of Lupe Velez, author Eve Golden uses extensive research to parse fact from fiction and offer a thorough, riveting, and comprehensive examination of the real woman underneath the gossip columns' caricature. Through astute analysis of the actress's iconic filmography and interviews, Golden illuminates the path Velez blazed through Hollywood. Her success was unexpected and extraordinary at a time when her distinctive accent was an obstacle, yet very few published books have focused entirely on Velez's life and career. Written with even-handedness, humor, and empathy, Golden has finally given the remarkable Mexican actress the uniquely nuanced portrait she deserves"--